2002
DOI: 10.5301/jbm.2008.5044
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of single and dual platform methodologies for the estimation of CD34+ hematopoietic progenitor cells: Correlation with colony assay

Abstract: In this study three assays for the enumeration of CD34+ progenitors were compared: 1) a modified version of the Milan protocol, used in the standard dual-platform format; 2) a dual-platform version of the ISHAGE protocol; 3) the ProCOUNT software version 2.0/ProCOUNT kit. The assays were compared to validate the accuracy of CD34+ cell counts in mobilized peripheral blood (PB), apheresis products (AP), and cord blood (CB). The ProCOUNT protocol uses reference beads for absolute CD34+ cell counting, whereas CD34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 0 publications
0
11
0
2
Order By: Relevance
“…The interprotocol variability issue has been addressed in the past by several groups. Moretti and coworkers 13 reported a good correlation between the ISHAGE protocol and a commercial single‐platform system (ProCOUNT, BD Biosciences, San Jose, CA) when analyzing peripheral blood and leukapheresis samples, as long as the white blood cell (WBC) count did not exceed 25 × 10 9 per L. Correlation was reported as suboptimal when analyzing cord blood samples. Piedras‐Ross and coworkers 10 also found a good correlation between the use of the dual‐platform Milan protocol 5 and the single‐platform ProCOUNT method in peripheral blood and apheresis products, but an underestimation of CD34+ cells was observed by the use of the single‐platform method in marrow samples 14 .…”
Section: Discussionmentioning
confidence: 99%
“…The interprotocol variability issue has been addressed in the past by several groups. Moretti and coworkers 13 reported a good correlation between the ISHAGE protocol and a commercial single‐platform system (ProCOUNT, BD Biosciences, San Jose, CA) when analyzing peripheral blood and leukapheresis samples, as long as the white blood cell (WBC) count did not exceed 25 × 10 9 per L. Correlation was reported as suboptimal when analyzing cord blood samples. Piedras‐Ross and coworkers 10 also found a good correlation between the use of the dual‐platform Milan protocol 5 and the single‐platform ProCOUNT method in peripheral blood and apheresis products, but an underestimation of CD34+ cells was observed by the use of the single‐platform method in marrow samples 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Use of HLA-A and -B serology and low-resolution allelic DRB1 typing showed that most of the children had either one (65%) or two (13%) disparities with their graft ( Table 2). The CD34 ĂŸ cell counts were analyzed by the two most commonly used CD34 ĂŸ cell quantification methods (ISHAGE protocol and ProCount; Becton Dickinson, Franklin Lakes, NJ, USA) 23 at 11 regional CB banks.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…CD34 enumeration was performed on viable cells with a dual-platform version of the ISHAGE protocol; 22 briefly, the WBC were measured with an automated hematology analyzer and, if necessary, samples were diluted; 100 ml aliquots of the sample, containing between 5 Â 10 6 and 10 Â 10 6 cells, were incubated for 30 min at 41C with 10 ml of phycoerythrin (PE)-conjugated anti-CD34 (HPCA-2), 10 ml of fluorescein isothiocyanate (FITC)-conjugated anti-CD45 (2D1) (BD Biosciences) and 20 ml of 7-aminoactinomycin D (final concentration 1 mg/ml). After incubation, the red cells were lysed and cells were analyzed by fluorescenceactivated cell sorting (FACScan, Becton Dickinson) using the CellQuest Software.…”
Section: Patient Populationmentioning
confidence: 99%